Weakly Sub-Gaussian Random Elements in Banach Spaces - Vakhaniya, N. N.; Kvaratskheliya, V. V.; Tarieladze, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We give a survey of properties of weakly sub-Gaussian random elements in infinite-dimensional spaces. Some new results and examples are also given.